Anti-Peroxyl Radical Quality and Antibacterial Properties of Rooibos Infusions and Their Pure Glycosylated Polyphenolic Constituents - Lissi-Gervaso, E (2013)
The anti-peroxyl radical quality of two aqueous rooibos infusions and solutions of their most abundant glycosylated polyphenols was evaluated using pyrogallol red and fluorescein-based oxygen radical absorbance ratios. It was observed that the artificial infusions, prepared using only the most abundant polyphenols present in rooibos and at concentrations similar to those found in the natural infusions, showed greater antioxidant quality than the latter infusions, reaching values close to those reported for tea infusions. Additionally, the antimicrobial activity of the natural and artificial infusions was assessed against three species of bacteria: Gram (+) Staphylococcus epidermidis and Staphylococcus aureus and Gram (-) Escherichia coli. When compared to the natural infusions the artificial beverages did not demonstrate any bacterostatic/cidal activity, suggesting that the antibacterial activity of rooibos is related to compounds other than the glycosylated polyphenols employed in our study. © 2013 by the authors.